Promoting Female Labor Force Participation - Pimkina, Svetlana (World Bank, Washington, DC, 2020)
Women comprise half of the world’s adult population, and therefore potentially half of its labor force. Removing barriers that restrict women from entering the labor market is crucial for achieving equality, as well as to untap economic growth. The focus of this review is on female labor force participation (FLFP) instead of employment. Labor force participation captures the decision to actively engage with the labor market, while employment represents an equilibrium outcome. The distinction is often under-emphasized, but it is not trivial, as these indicators move separately. Indeed, the global rate of female employment has remained high at around 94 percent, while the rate of FLFP has not yet surpassed 50 percent. This review identifies constraints around three key drivers of FLFP. First, the authors examine how constraints in endowments such as time, education, financial and social capital limit women’s participation. Second, authors review evidence on the role of internal factors such as choices, preferences, norms and beliefs on FLFP. Third, authors discuss how external constraints such as income shocks and demand-side factors inhibit active engagement in the labor market. Finally, the paper concludes with some lesson learned from policies to improve FLFP and draws up an agenda for future research.